A marginal level of dystrophin partially ameliorates hind limb muscle passive mechanicalf properties in dystrophin-null mice - Hakim, Chady H. (2012)
INTRODUCTION: The goal of this study was to determine whether a minimal level of dystrophin expression improves the passive mechanical properties of skeletal muscle in the murine Duchenne muscular dystrophy model. METHOD: We compared the elastic and viscous properties of the extensor digitorum longus muscle (EDL) in mdx3cv and mdx4cv mice at 6, 14 and 20 months of age. Both strains are on the C57Bl/6 background, and both lose the full-length dystrophin protein. Interestingly, mdx3cv mice express a near full-length dystrophin at ~5% of the normal level. RESULT: We found that the stress-strain profile and the stress relaxation rate of the EDL in mdx3cv mice were partially preserved in all age groups compared to that of age-matched mdx4cv mice. DISCUSSION: Our results suggest that a low-level of dystrophin expression may treat muscle stiffness in Duchenne muscular dystrophy.